Design and Realization of Jiujiang Urban Smart Water Platform Based on Digital Twin Technology - CHEN Guobiao (Renmin Zhujiang)
Nowadays,the digital technology based on digital twin is becoming increasingly mature.To make the water environment treatment of the Yangtze River stable and efficient for a long time,Shanghai Investigation,Design & Research Institute (SIDRI) adopted the advanced concept of smart water in the water environment treatment of the central urban area in Jiujiang,the first pilot city of the Yangtze River Protection,and developed a smart water platform with the digital twin as a core technology.With the digital twin technology,SIDRI built the data base of the city and applied the smart water platform combined with 5G Internet of things,hydraulic modeling and cloud computing technology.Integrating the data of river water regime,water quality,regional rain regime,pump station operation,real-time monitoring of pipe network and other water management content,SIDRI created a spatial-temporal model of the water environment in Jiujiang central urban area with the platform,which improves the efficiency of comprehensive treatment and integrated operation of “plant-network-river-lake-(bank).” The platform can help real-time effective supervision and scientific decision-making of water treatment and provide reference for future smart water development.